Analysis of the genotype–phenotype correlation in isovaleric acidaemia: A case report of long-term follow-up of a chinese patient and literature review - Liu, Xingmiao; Liu, Xinquan; Fan, Wenxuan; Zhang, Zhongbin; Zhang, Peiyuan; Liu, Xiaojun; Lei, Meifang; Li, Qing; Yu, Xiaoli; Li, Dong (Frontiers in Neurology, 2022)
Background: Isovaleric acidaemia (IVA), characterised by an acute metabolic crisis and psychomotor delay, is a rare inherited metabolic disease caused by a deficiency in isovaleryl-CoA dehydrogenase (IVD). Methods: We report the case of a Chinese patient with IVA admitted to Tianjin Children’s Hospital and followed up for 8 years. Genetic analysis of the patient and his parents was conducted using whole-exome gene sequencing and Sanger sequencing. We searched for similar reported cases in the PubMed and Wanfang databases using the term “isovaleric acidaemia,” reviewed the related literature to obtain a summary of the clinical and genetic characteristics, and analysed the genotype–phenotype correlations. Results: The patient presented with encephalopathic symptoms such as vomiting, lethargy, and somnolence. We identified complex heterozygous variants of the IVD gene, including the unreported variant c.224A>G (p.Asn75Ser) and the reported variant c.1195G>C (p.Asp399His). The child was prescribed a low-protein diet supplemented with L-carnitine. During the 8-year follow-up, no metabolic disorder or encephalopathic symptoms recurred. At present, the child is 11 years of age and has normal mental and motor performance. Another 154 cases identified in 25 relevant references were combined with this case, resulting in a sample of 155 patients, including 52 asymptomatic patients, 64 with neonatal onset, and 39 with chronic intermittent disease with onset from ages 1 month to 10 years (median age, 2 years). Among articles that reported sex, the male-to-female ratio was 1:1.06. The cardinal symptoms included vomiting, lethargy, “sweaty foot” odour, poor feeding, developmental delay, and epilepsy. The proportion of variants in regions 123–159 and 356–403 of the IVD protein was greater in symptomatic patients than in asymptomatic patients. Conversely, in asymptomatic patients, the proportion of variants in the 282–318 region was greater than in symptomatic patients. Conclusion: This case report describes a unreported variant c.224A>G (p.Asn75Ser) of the IVD gene, and summarizes previously reported cases. Furthermore, the correlation between the genotype and clinical phenotype of IVA is analysed to improve the understanding of this disease.